Sequential changes in oligoclonal patterns during the course of multiple sclerosis. Issue 2 (February 1983) - Thompson, E J; Kaufmann, P; Rudge, P
Abstract : The majority of patients with multiple sclerosis have an abnormality of their spinal fluid immunoglobulins. This alteration is manifested as patterns of diffuse protein bands in the gamma globulin region following electrophoresis. This pattern has been termed one of restricted heterogeneity, or an oligoclonal pattern. We have found changes in the banding pattern of some patients studied longitudinally. Since the significance of these findings may be relevant to the pathogenesis of this notoriously waxing and waning disease, we discuss the importance of methodologies as well as the concept that IgM and IgA may be relevant to the interpretation of these observations.